Lean manufacturing model for the reduction of production times and reduction of the returns of defective items in textile industry - Andrade, Yanira (Springer, 2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado. === Textile garment industries must be readily aware of the system’s current situation, respond quickly to changes in style to process orders on time, and manage an appropriate method of work to avoid production delays. In addition, the textile sector plays an important role because it presents a significant weight in the world economy. Likewise, this sector is considered influential when defining an international business agreement. Therefore, adequate management is required in the sector. Otherwise, it will generate a competitive disadvantage because the Peruvian industry is approaching an export recession. This paper proposes using the lean manufacturing methodology to reduce production times. The project is validated through a simulation of the current and proposed processes with the application of lean thinking tools to reduce waste (manufacturing process times).